Multiple Myeloma with Foamy Mott Cells - Nalbandyan, Karen; Benharroch, Daniel; Samueli, Benzion; Kafka, Michael; Gourevitch, Anna (Case Reports in Hematology, 2021)
Intracytoplasmic assorted vacuoles containing immunoglobulin collections are occasionally seen in multiple myeloma. When abundant, they impart a foamy appearance to the tumor cells, which is a potential source for diagnostic pitfalls. Herein, we report the case of a patient who presented with skeletal pain and CT confirmed lytic lesions. A bone marrow biopsy revealed multiple myeloma with unusual foamy Mott cells. The patient was subsequently treated with four cycles of cyclophosphamide, bortezomib, and dexamethasone induction therapy, followed by 3 cycles of lenalidomide with dexamethasone. A biopsy performed following initial biological and immunomodulatory drugs revealed different morphological and clonal characteristics. These features were modified again, five years later, and again, after two years of close monitoring. Hematopathologists should be aware of this morphologic variant of myeloma as well as for the capacity of clonal characteristics, such as light chain monotype, to fluctuate subsequent to treatment.